The Student as Own-Therapist: Self Control Procedures for Use in Today's Schools and Universities - Andrews, W. R.; Marshall, W. L. (Canadian Journal of Counselling and Psychotherapy, 2012)
Self-control procedures are discussed as a new tool of the counsellor for helping clients. Goal-setting by the client, and how he can effectively use the environment in achieving his goals, are considered both philosophically and technically. Thoresen and Mahoney's classifications of environmental planning and behavioral programming are used to order the presentation of systematic desensitization, operant and coverant techniques, all as self-administered procedures.Comment is offered upon self-observation and recording, client ageand maturity, perfectionism and the limits of self-control, the need for some counsellor-client contact, and ways of mediating self-control procedures so as to reach crisis-relevant and developmental objectives. Les procédures de maîtrise de soi sont discutées comme un nouveau moyen dont dispose le conseiller pour aider ses clients. Les buts quele client veut atteindre, et comment il peut employer son milieu efficacement pour atteindre ses buts, sont considérés philosophiquement et théoriquement.Les classifications de système de Thorensen et de Mahoney sur lemilieu et sur le plan de conduite sont utilisées pour fixer l'ordre dela présentation de 'desensitization' systématique et des techniques 'operant'et 'coverant'.On offre des commentaires sur l'observation de soi, l'âge et la maturitédu client, le perfectionnement et les limites de la maîtrise de soi, le besoin de rapport entre le conseiller et son client, et les méthodes pourprocurer la maîtrise de soi afin d'atteindre les buts relatifs à la solutiondu problème particulier et au développement de la personne.